2019
DOI: 10.1055/s-0039-1696672
|View full text |Cite|
|
Sign up to set email alerts
|

A Randomized Controlled Single-Blind Study Demonstrating Superiority of Amniotic Suspension Allograft Injection Over Hyaluronic Acid and Saline Control for Modification of Knee Osteoarthritis Symptoms

Abstract: Placental-derived tissues are a known source of anti-inflammatory and immune modulating factors. Published pilot data on amniotic suspension allograft (ASA) for the treatment of osteoarthritis (OA) demonstrated safety and trends for improved pain and function. A multicenter randomized controlled trial was designed to evaluate the efficacy of symptom modulation with ASA compared with saline and hyaluronic acid (HA) in subjects with knee OA. A total of 200 subjects were randomized 1:1:1 to ASA, HA, or saline, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…That subsequent study (ClinicalTrials.gov Identifier: NCT02318511) comprised 200 OA patients randomized to receive a single injection of ASA, hyaluronic acid, or saline. Subjects who received ASA injections demonstrated superior efficacy in measures of pain and function at 3 and 6 months post-treatment 43 . In a separate study, a noted reduction in pain at 6 months post-injection was reported for 20 OA patients that were treated with an IA injection of morselized amniotic membrane/umbilical cord tissue 44 .…”
Section: Discussionmentioning
confidence: 93%
“…That subsequent study (ClinicalTrials.gov Identifier: NCT02318511) comprised 200 OA patients randomized to receive a single injection of ASA, hyaluronic acid, or saline. Subjects who received ASA injections demonstrated superior efficacy in measures of pain and function at 3 and 6 months post-treatment 43 . In a separate study, a noted reduction in pain at 6 months post-injection was reported for 20 OA patients that were treated with an IA injection of morselized amniotic membrane/umbilical cord tissue 44 .…”
Section: Discussionmentioning
confidence: 93%
“…At 6 months posttreatment, the ASA group had significantly greater improvement from baseline in J o u r n a l P r e -p r o o f multiple PRO subsets as compared to the HA and saline groups, with a significantly greater responder rate (69.1%) in the ASA group. They concluded that ASA injections produce a clinically meaningful improvement in symptoms of knee OA as compared to HA and saline injections 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Amniotic tissue was initially described for clinical use as a biologic dressing for skin defects 9 . Uses of amniotic membrane tissue have evolved to include treatment for ophthalmologic conditions, complex wounds, and more recently for orthopedic conditions such as tendinopathy and osteoarthritis [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By 2030, the number of US adults with arthritis is expected to reach 67 million, leading to a continuous increase in the number of total knee replacement surgeries [ 2 – 4 ]. While total knee replacement surgeries have shown advantages, avoiding or delaying such surgery is usually desirable, for medical reasons and health care system perspective [ 5 ]. The long-term outcomes after total knee replacement surgeries for patients with grade II or III knee OA on the Kellgren-Lawrence (KL) scale are worse compared to patients with grade IV OA [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%